The efficacy and safety of a novel PD‐1/CTLA‐4 bispecific antibody cadonilimab (AK104) in advanced non‐small cell lung cancer: A multicenter retrospective observational study - Hongxin Li; Wen Zhao; Chengming Li; Hongchang Shen; Meiying Li; Chengjun Wang; Chunyan Han; Cuihua Yi; Jun Wang; Xue Meng; Lian Liu; Shuwen Yu; et al. (Thoracic Cancer)
Abstract Background For patients with advanced non‐small cell lung cancer (NSCLC) who have received frontline immunochemotherapy, subsequent treatment options are limited. As the first dual programmed cell death‐1 (PD‐1)/cytotoxic T lymphocyte‐associated antigen‐4 bispecific antibody approved globally, cadonilimab demonstrated potential antitumor activity in advanced NSCLC patients resistant to anti‐PD‐1/PD‐L1 antibodies. Methods We retrospectively collected efficacy and safety data from advanced NSCLC patients treated with cadonilimab‐based regimens in later therapy lines. Results A total of 41 advanced NSCLC patients refractory to anti‐PD‐1/PD‐L1 therapy were enrolled. More than half of the patients received cadonilimab‐based regimen as a fourth or later line of treatment. At the data cutoff date, treatment efficacy could be evaluated in 23 patients. One patient (4.3%) achieved partial response, eight patients (34.8%) experienced stable disease, and 14 patients (60.9%) progressed. The objective response rate and disease control rate were 4.3% and 39.1%, respectively. The median progression‐free survival for all evaluated patients was 108.0 days. Due to the short follow‐up period, the median overall survival has not yet been reached. Treatment‐related adverse events (TRAEs) and immune‐related AEs occurred in 63.4% and 22% patients, respectively. The most common TRAEs included gamma‐glutamyl transferase elevation (17.1%), coughing (14.6%), and fatigue (12.2%). Five patients (12.2%) experienced grade ≥3 TRAEs. Conclusions In this heavily pretreated cohort of advanced NSCLC patients, cadonilimab‐based regimens showed moderate antitumor efficacy with a generally tolerable and manageable safety profile. However, more evidence is needed to support the administration of cadonilimab in NSCLC patients refractory to previous anti‐PD‐1/PD‐L1 therapy.